2D Virtual Reality-Based Exercise Improves Spatial Navigation in Institutionalized Non-robust Older Persons: A Preliminary Data Report of a Single-Blind, Randomized, and Controlled Study - Oliveira, Luciana Mendes; Evangelista e Souza, Eric Hudson; Alves, Mariana Rocha; Carneiro, Lara S. F.; Fagundes, Daniel Ferreira; de Paula, Alfredo Maurício Batista; Engedal, Knut; Nascimento, Osvaldo J. M.; Monteiro-Junior, Renato Sobral (Frontiers in Neurology, 2021)
Background: Spatial navigation is a prodromal dementia marker. Exercise used alongside virtual reality improves many cognitive functions, but effects on spatial navigation are still unclear. Objective: To investigate the effect of virtual reality-based physical exercise with 2D exergames on spatial navigation in institutionalized non-robust older persons. Method: A total of 14 older persons (aged ≧ 60) were randomly allocated to the exergame (EG) and active control (ACG) groups. EG performed exercises with 2D exergames, while the ACG used the same movements as the EG, but without the use of virtual reality. Spatial navigation was assessed through the Floor Maze Test, where the immediate maze time (IMT) and delayed maze time (DMT) were recorded. Results: Spatial navigation was enhanced in EG participants compared to ACG individuals. A significant (p = 0.01) IMT reduction between groups was observed, while DMT time without prior planning was significantly different at the significance threshold (p = 0.07). Conclusions: Virtual reality-based exercise improves the spatial navigation of institutionalized non-robust older persons. This study should be replicated to confirm the findings reported herein. Clinical Trial Registration: This study was registered in the Brazilian Registry of Clinical Trials (Protocol RBR-8dv3kg - https://ensaiosclinicos.gov.br/rg/RBR-8dv3kg).